VALIDACIÓN DE UNA METODOLOGÍA ANALÍTICA PARA LA CUANTIFICACIÓN DE AMINOÁCIDOS EN EL PEZ Anisotremus scapularis “Chita” - Ruiz Soto, Anthony (2024)
The Anisotremus scapularis “Chita” is a species that lives on the coast of Peru and is considered potential for fish farming. Studies on the amino acid profile have not yet been reported. The aim of this investigation was to developed an analytical method for the quantification of amino acids in lyophilized muscle from the Chita by HPLC-FL. To achieve this objective, the hydrolysis conditions was optimized, as a result, the HCl concentration, hydrolysis time and temperature were 6 M, 24 h and 100 °C respectively. The results of the most relevant performance parameters were: the linearity had a coefficient of determination (R2>0,999), the accuracy showed that all amino acids did not exceed the bias of 15%. The recovery ranged from 97,08% to 102,44%. The coefficients of variation for repeatability and intermediate precision were ranging from 1,93% to 5,43% and 2,08% to 10,69% respectively. The LOD and LOQ were ranging from 0,002 to 0,014 g/100 g and 0,005 to 0,043 g/100 g respectively. The robustness showed that the method is sensible to changes to the studied factors. Finally, the method met the majority of acceptance criteria, and it is suitable for the analysis of amino acids in Chita.